Making sense of history: narrativity and literariness in the Ottoman Chronicle of Na'ima - Şen, Gül (Brill, 2022)
The life and career fo Naʻīmā Muṣṭafā Efendi in historical context -- Court chronicles as a genre in the context of Ottoman historiography -- General literary features -- Interpolations -- Analysis of surface structure -- Analysis of the narrative structure -- Creating continuity : the concept of history -- The concept(s) of Time -- Strategies to cope with experiences of contingency.
Gesehen am 23.09.2022
Includes bibliographical references and index
Keywords: Naima, Mustafa -- 1655-1716 -- Tarih-i Naima; Turkey -- History -- 1288-1453 -- Early works to 1800; Turkey -- History -- 1453-1683 -- Early works to 1800; Turkey -- Historiography; Erzähltheorie; Geschichtsschreibung; Naima